Balkan syntax and semantics - Tomić, Olga Mišeska (Linguistik aktuell ;, 2004)
The book deals with some syntactic and semantic aspects of the shared Balkan Sprachbund properties. In a comprehensive introductory chapter, Tomic offers an overview of the Balkan Sprachbund properties. Sobolev, displaying the areal distribution of 65 properties, argues for dialect cartography. Friedman, on the example of the evidentials, argues for typologically informed areal explanation of the Balkan properties. The other contributions analyze specific phenomena: polidefinite DPs in Greek and Aromanian (Campos and Stavrou), Balkan constructions in which datives combine with impersonal cliti.